Stanowisko Parlamentu Europejskiego wobec problemu proliferacji broni masowego rażenia i terroryzmu międzynarodowego - Staszczyk, Artur (Przegląd Strategiczny, 2016)
The paper presents the stance of the European Parliament (EP) on the gravest threats to the security of the EU, in particular, the proliferation of weapons of mass destruction and the issue of international terrorism. Prevention of these threats lies predominantly within the competence of EU member states and its intergovernmental bodies. Such situation is implied by the fact that these issues fall within the scope of EU’s Common Foreign and Security Policy (CFSP) within which intergovernmental collaboration mechanisms play a dominant role. This means that the EP’s role in the shaping of EU’s policy on the prevention of weapons of mass destruction proliferation and international terrorism is limited and basically confined to the expression of non-binding opinions in its resolutions. However, relevant resolutions passed by the EP, though not binding in legal terms, have political significance and allow the EP, in contrast to other EU’s institutions, to articulate its position in an unequivocal and clear way. This is possible since the EP is the only supranational EU institution that has democratic legitimacy and can claim the right to exercise parliamentary control over the EU’s policy with respect to the prevention of the gravest threats to European security. This is particularly vivid as it comes to the fight against terrorism which is also the subject of interest for the common space of freedom, security and justice which employs intragovernmental collaboration mechanisms.